Satellite detection of wastewater diversion plumes in Southern California. (15th February 2017) - Gierach, Michelle M.; Holt, Benjamin; Trinh, Rebecca; Jack Pan, B.; Rains, Christine
Abstract: Multi-sensor satellite observations proved useful in detecting surfacing wastewater plumes during the 2006 Hyperion Treatment Plant (HTP) and 2012 Orange County Sanitation District (OCSD) wastewater diversion events in Southern California. Satellite sensors were capable of detecting biophysical signatures associated with the wastewater, compared to ambient ocean waters, enabling monitoring of environmental impacts over a greater spatial extent than in situ sampling alone. Thermal satellite sensors measured decreased sea surface temperatures (SSTs) associated with the surfacing plumes. Ocean color satellite sensors did not measure a distinguishable biological response in terms of chlorophyll-a (chl-a) concentrations during the short lived, three-day long, 2006 HTP diversion. A period of decreased chl-a concentration was observed during the three-week long 2012 OCSD diversion, likely in association with enhanced chlorination of the discharged wastewater that suppressed the phytoplankton response and/or significant uptake by heterotrophic bacteria. Synthetic aperture radar (SAR) satellite data were able to identify and track the 2006 HTP wastewater plume through changes in surface roughness related to the oily components of the treated surfacing wastewater. Overall, it was found that chl-a and SST values must have differences of at least 1 mg m −3 and 0.5 °C, respectively, in comparison with adjacent waters for wastewater plumes and their biophysical impact to be detectable from satellite. For a wastewater plume to be identifiable in SAR imagery, wind speeds must range between ∼3 and 8 m s −1 . The findings of this study illustrate the benefit of utilizing multiple satellite sensors to monitor the rapidly changing environmental response to surfacing wastewater plumes, and can help inform future wastewater diversions in coastal areas.